Synthesizing Highly Fluorinated Oligophenyls via Negishi Coupling of Fluoroarylzinc Pivalates - Stoesser, Julian; Engelage, Elric; Huber, Stefan M. (Synthesis, 2021)
Previously established general synthetic methods for the synthesis of highly fluorinated biphenyls using Suzuki–Miyaura protocols require the use of organoboron compounds, which are not very stable under reactions conditions and thus need to be used in large excess. Herein, we report an improved general strategy for the synthesis of highly fluorinated biphenyls, terphenyls, and phenyl-substituted terphenyls using organozinc pivalates. The influence of several parameters was investigated: (1) in a series of monodentate phosphine ligands, X-Phos showed the best performance; (2) a higher yield was obtained for substrates bearing less steric hindrance or lower amount of fluorine substitution; (3) as iodinated substrates decomposed during the reaction, brominated electrophiles were found to be superior. The presented protocol is scalable, versatile, and works with commonly used and commercially available phosphine ligands (X-Phos) and palladium sources (Pd2dba3). Also, it does not require excess nucleophile for terphenyl synthesis and only a slight excess is needed for the preparation of phenyl substituted terphenyls.
Keywords: polyfluorinated compounds; biphenyls; Negishi coupling; electron-poor substrates; terphenyls; organozinc species